PELATIHAN INTEGRASI KECERDASAN BUATAN DALAM PENGEMBANGAN BAHAN AJAR INTERAKTIF UNTUK GURU DI SEKOLAH TUNAS JAKASAMPURNA - Afifah Arifuddin, Nurul; Dwi Amalia, Rifka; Setyadinsa, Radinal (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of technology in education has seen rapid development over the past few decades, with Artificial Intelligence (AI) becoming one of the most prominent technologies. AI has the potential to enhance the effectiveness and efficiency of teaching and learning processes, particularly in the development of interactive teaching materials. The training titled "Integration of Artificial Intelligence in the Development of Interactive Teaching Materials," held on May 17, 2024, at Tunas Jakasampurna School, aimed to improve teachers' understanding and skills in using AI. This training was attended by 35 teachers and involved lectures, demonstrations, and hands-on practice using AI applications such as ChatGPT and Gemini. Before the training, a pretest was conducted to assess participants' initial understanding of AI. The pretest results showed varying levels of understanding among teachers, with average scores ranging from 2.4 to 3.4 on a Likert scale of 1-5. Post-training results indicated a significant increase in teachers' understanding and skills, with average scores ranging from 4.4 to 4.8. The training successfully enhanced teachers' knowledge and confidence in using AI to develop interactive teaching materials. Participants also expressed high satisfaction with the training and plan to continue developing their skills in this field.